Planning the microsurgical myelotomy in intramedullary tumors or cysts by intraoperative neuromonitoring - Borut Prestor (Zdravniški Vestnik, 2005)
Background: Surgical approach to the intramedullary tumors and cavities are microsurgical techniques of dorsal myelotomies, which entails the risk of damage to the dorsal columns and the central spinal cord gray matter. The aim of the study is to analyze the clinical sensory dysfunction before surgery and the changes of the intraoperative SEP (somatosensory potentials) before myelotomy. These data would be of help to neurosurgeons in planning the myelotomy – dorsomedial or dorsolateral. Methods: 16 patients were operated on for deafferentation pain syndromes, intramedullary tumors and syringomyelia of the cervical spinal cord. Preoperatively the patients sensory system of dorsal columns and central gray matter was examined for vibration and position sense dysfunction and pain and temperature damage. Before myelotomy the intraoperative SEP from the dorsal surface of the spinal cord after the stimulation of the median and tibial nerves were recorded. Results: After median nerve stimulation the N13 wave was partially or completely absent, and fast negative waves appeared instead. The presence and absence of N13 was in association with pain and temperature dysfunction or with dissociative sensory loss. The mean duration of the SEP potential was shorter than normal (p < 0.0005, n = 11). After tibial nerve stimulation the first negative waves were most stabile, fast negative waves as the most prominent element of the normal SEP were partially or completely absent. This change was in association with diminution or loss of vibration and posture senses. The duration of the conductive SEP was shorter than normal (p = 0.064, n = 5). Conclusions: Dissociative sensory loss is associated with absence of the N13 in median nerve SEP and connected to the central cord destruction. The loss of vibration and posture senses affects the fast negative waves of tibial SEP and points toward damage of the dorsal columns. The dorsolateral myelotomy is justified in cases of central cord destruction, and dorsomedial myelotomy in cases of dorsal columns damage.